2017
DOI: 10.1097/md.0000000000006285
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative ultrasound-guided carbon nanoparticles localization for metastatic lymph nodes in papillary thyroid carcinoma during reoperation

Abstract: Due to the damaged anatomical structure and a large amount of fibrous and scar tissues in the surgical field, reoperation of papillary thyroid carcinoma is difficult. This study introduces a new method of locating metastatic lymph nodes during reoperation and evaluates the effectiveness and safety of the preoperative ultrasound-guided carbon nanoparticles (CNs) localization. This retrospective cohort study enrolled 52 patients who were diagnosed with lymph node metastasis by histopathology and underwent reoper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 31 publications
3
28
0
Order By: Relevance
“…A previous study recruited 110 patients with an identification rate of 96.4% by SLN-CEUS, and the median number of SLNs detected by CEUS was 1.2. SLN-CEUS had a 100% sensitivity, 52.0% specificity, 64.9% accuracy, 43.4% positive predictive value and 100% negative predictive value in identifying metastatic LNs (Zhao et al 2017). Another study recruited 101 patients, and the sensitivity and specificity were 81.8% and 86.2%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study recruited 110 patients with an identification rate of 96.4% by SLN-CEUS, and the median number of SLNs detected by CEUS was 1.2. SLN-CEUS had a 100% sensitivity, 52.0% specificity, 64.9% accuracy, 43.4% positive predictive value and 100% negative predictive value in identifying metastatic LNs (Zhao et al 2017). Another study recruited 101 patients, and the sensitivity and specificity were 81.8% and 86.2%.…”
Section: Discussionmentioning
confidence: 99%
“…If no enhanced LCs were observed after massaging around the areola, the second injection of contrast agent was performed to re-assess the enhancement of LCs and SLNs according to the previous procedure. The patterns of enhancement in SLNs can be classified as follows: homogeneous enhancement, inhomogeneous enhancement and no enhancement (Sharma and Cox 2017;Zhao et al 2017). In this study, homogeneously enhanced SLNs were considered to be non-metastatic nodes.…”
Section: Quality Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 19 ] Moreover, CNs was safety and nontoxic to date. [ 20 22 ] Therefore, we conducted the retrospective study to evaluate the function of CNs as lymph nodes tracer during thyroid reoperation.…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid cancer is the most common endocrine malignant tumor, and the most common pathological type is papillary thyroid cancer (PTC), accounting for more than 90% of the total thyroid cancer [1][2] .Surgical treatment is the main treatment of this disease 3 ,because of its high rate of lymph node metastasis 4] therefore, the routine cervical lymph node dissection in China increases the injury rate of parathyroid gland and the risk of postoperative hypocalcaemia with the expansion of surgical scope 5 .Studies have shown that carbon nanoparticles can darken lymph nodes and negatively develop parathyroid glands 6 ,it is widely used in thyroid surgery, but whether carbon nanoparticles have a protective effect on parathyroid glands is controversial 10,17 .The purpose of this study was to investigate the value of carbon nanoparticles in thyroid cancer surgery and cervical central lymph node dissection.…”
Section: Introductionmentioning
confidence: 99%